Dental Caries Prevalence, Restorative Needs and Oral Hygiene Status in Adult Population - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Dental caries affects the quality of life and it is the most common oral health challenges worldwide. While dental caries prevalence is well documented to be declining in many developed countries, the prevalence among adult population in Nigeria is yet to be fully documented.Aim:This study aimed to determine dental caries prevalence, restorative needs, and oral hygiene status among nurses.Materials and Methods:This was a descriptive cross-sectional study. The study participants were recruited by simple random sampling technique. The nurses' caries status was determined using the WHO-recommended D-decayed, M-missing, F-filled, T-teeth (DMFT) index. Restorative index was used to determine the restorative needs while simplified oral hygiene index (OHI-S) by Green and Vermilion was adopted for the assessment of oral hygiene status.Statistical Analysis Used:Descriptive statistics and Chi-squared tests were used for data analysis. This was done using SPSS version 23.0.Results:A total of 251 subjects participated in this study. The age range was 19–64 years, and the mean age was 38 ± 9.88. Among the participants, 60.6% have experienced dental caries inform of filled, decayed and missing teeth. Dental caries prevalence was 43.8% and the mean DMFT was 2.06 ± 2.46. Met need index and restorative index were 0.46 and 14.6% respectively. Using OHI-S, 22.7% had good, 66.1% fair, and 11.2% had poor oral hygiene status.Conclusion:The prevalence of dental caries among nurses 'the adults' study population was high with low secondary prevention and low Restorative index. Majority had 'fair' Oral hygiene status.